Binnatov, Yusif - (:unkn) unknown (My University, 2026)
Yusif Javad Binnatov graduated from the Azerbaijan Civil Engineering University (now Azerbaijan University of Architecture and Construction – AzUAC) in 1999 with a Bachelor’s degree in Economics and Management of Construction. He subsequently completed a Master’s degree with distinction in Marketing (Construction) at AzUAC. Since 2002/2003, he has been working at AzUAC. From 2003 to 2009, he served as a Senior Laboratory Assistant at the Department of Economic Theory and Marketing, followed by positions as Lecturer and, since 2018, Senior Lecturer. He teaches Introduction to Economics, Microeconomics, Macroeconomics, Marketing, and Economy of Azerbaijan. In 2025, he successfully defended his PhD dissertation, Formation and Improvement of Economic Relations in the Construction Sector of Azerbaijan, in the specialty 5312.01 – Sectoral Economics. By the decision of the Higher Attestation Commission dated 16 March 2026, he was awarded the degree of Doctor of Philosophy (PhD) in Economics. Dr. Binnatov is the author of more than 50 scientific publications and numerous course programmes. His research has been published in Azerbaijan and internationally, and he has participated in national and international scientific conferences. His research interests include economic relations and development in the construction sector, economics, and marketing.